Pengembangan jenjang karir perawat manajer di rumah sakit - Wahyu Kusumadi Retnoningtyas; Hanny Handiyani; Nurdiana Nurdiana (Holistik Jurnal Kesehatan, 2020)
Becoming a Nurse Manager: A career track and system in hospitalBackground: Nurse career pathway is very effective to support career development, increase retention and facilitate self actualization of nurses. Regulations on the nurse manager’s career pathway are developed in line with the clinical nurse’s professional career pathway.Purpose: Identify and analyze needs related to the development of career path system for nurse managersMethod: A pilot project starting from data collection, problem analysis, problem priority setting, develop plan of action, implementation and evaluation. Respondents are the head nurseas many as 74 people and the nursing staff as many as 110 people. Problem analysis used fishbone diagrams.Results: The problem that arises is the lack of optimal development of manager nurses 'career levels caused by the absence of guidelines for manager nurses' career paths, the SOP has not been compiled yet, there are nurse managers who have DIII nursing education degree, many self-assessment results of the head nurses are still feeling incompetent, nursing staff perception about the ability of the head nurse is not optimal in carrying out their roles and functions .Conclusion: The implementation given as a solution to the problem  that is making guidelines for nurse managers career pathway and writing the manuscript. The recommendation for hospitals is that guidelines are adopted so that the mechanism for career advancement can be implemented.Keywords: A career track; Competency, Continuous professional development; Nurse manager; HospitalPendahuluan: Jenjang karir perawat sangat efektif menunjang perkembangan karier, meningkatkan retensi, dan memfasilitasi aktualisasi diri perawat. Regulasi tentang jenjang karir perawat manajer mulai dikembangkan sejalan dengan jenjang karir professional perawat klinis.Tujuan: Mengidentifikasi  dan  menganalisis kebutuhan  terkait  pengembangan pola jenjang karir bagi para perawat manajerMetode: Pilot project mulai dari pengumpulan data, analisis masalah, penetapan prioritas masalah, penyusunan plan of action, implementasi dan evaluasi. Responden adalah kepala ruangan sebanyak 74 orang dan staf perawat sebanyak 110 orang. Analisis masalah dilakukan dengan menggunakan diagram fishbone.Hasil: Didapatkan masalah belum optimalnya pengembangan jenjang karir perawat manajer yang disebabkan belum adanya panduan pola jenjang karir perawat manajer, belum disusunnya SPO, masih ada perawat manajer yang berpendidikan DIII keperawatan, hasil self assessment kepala ruangan masih banyak yang merasa belum kompeten, staf perawat menilai kemampuan kepala ruangan belum optimal dalam menjalankan peran dan fungsinya.Simpulan: Implementasi yang diberikan sebagai solusi permasalahan yaitu membuat panduan pola jenjang karir perawat manajer. Rekomendasi bagi rumah sakit yaitu panduan disahkan hingga mekanisme peningkatan jenjang karir dapat diimplementasikan.